A comparison of alternative vehicle fueling infrastructure scenarios. (1st February 2020) - Lane, Blake; Shaffer, Brendan; Samuelsen, Scott
Highlights: Infrastructure and emissions of conventional and alternative vehicles are analyzed. Alternative vehicle fuel supply chains dictate GHG and pollutant emission levels. Hybrid Electric and Plug-In Hybrid Electric Vehicles bridge to alternative vehicles. Range extended Plug-In Electric Vehicles have relatively low infrastructure costs. Plug-In Fuel Cell Electric Vehicles expedite the transition to alternative vehicles. Abstract: The evolution of alternative vehicles is leading to an evolution in fuel, from electricity to hydrogen, and the associated fueling infrastructure. Using California as an example and a variety of tools (e.g., vehicle and electric grid simulation, travel surveys, census data, and GIS analyses), fueling supply chain and dispensing scenarios are evaluated and compared for conventional internal combustion vehicles (ICVs), vehicles bridging from conventional to alternative vehicles such as hybrid electric vehicles (HEVs) and plug-in hybrid electric vehicles (PHEVs), and alternative vehicles including battery electric vehicles (BEVs), fuel cell electric vehicles (FCEVs), and plug-in fuel cell electric vehicles (PFCEVs). When assessed for a 2050 timeframe, PFCEVs require less electric infrastructure compared to BEVs, and less hydrogen infrastructure compared to FCEVs. In addition, until 100% zero-emission fuel supply chains are achieved, PFCEVs reduce GHG and CAP emissions to a greater extent than BEVs and FCEVs.